Optimal operation of combined cooling heat and power (CCHP) systems in future energy networks - Chen, Yumin (2017)
With the rapid development of energy internet, distributed energy resources and energy storage technology, the relationship between cooling, heat and power energy is getting closer and closer. It is evitable that combined cooling, heat and power energy (CCHP) system being widely used in the future. To optimize the operation of CCHP system, this study established a model of CCHP-based microgrid, considering energy storage, operation characteristics of different units and time-of-use electricity prices. Optimization methods based on PSO algorithm and Lingo software were used to minimize the total operational costs of microgrid in the scheduling period. Besides, comparison and discussion were made on three separate scheduling modes of microgrid in order to find the best and most cost-saving mode. The results of calculation indicate that the model established in this paper could effectively reduce the operational costs. Hoping that the outcome of this paper could serve as a reference for future studies on CCHP system-based microgrid.